The mechanical properties of anisotropic polymers - Darlington, M. (College of Aeronautics, 1966)
The work in this period can conveniently be split into two parts which are reported separately. Part I is concerned with experimental work on the stress-strain properties of anisotropic polythene. This work was initiated as a first step in the collection of data on anisotropic polymers. The results provide a very useful, general idea of the properties of a polymer, together with their variation with anisotropy. The experience gained during this work has also been of use when considering apparatus design details for creep measurements. Part II is concerned with the design of an apparatus for creep studies. The design considerations are discussed in Section 1; an outline of several design proposals being given in Section 2. The design project was started in the latter part of the period under review and therefore no comprehensive tests have yet been performed.